"Because I'm Old": The Role of Ageism in Older Adults' Experiences of Digital Literacy Training in Public Libraries. Issue 4 (22nd November 2021) - Barrie, Hannah; La Rose, Tara; Detlor, Brian; Julien, Heidi; Serenko, Alexander
Abstract: This article explores the experiences of older adults attending digital literacy training sessions offered by the public library system in one city in Ontario. Semi-structured interviews with 12 older adults (age 60+) demonstrated the significance of societal and internalized ageism in shaping the experiences of participants, as well as the construction of the training as a "safe space" for experimentation. Implications for participants and future public library digital literacy training sessions are discussed, with particular attention to asset-based approaches, the need for skill development, and addressing the effects of ageism on participants. Supplemental data for this article is available online at https://doi.org/10.1080/15228835.2021.1962477 .